Methodology for the investigation of crimes in the sphere of information security (Journal of actual problems of jurisprudence, 2018)
Data on information crimes are most often broken. In this connection, and in terms of forensic science, and practice to fully disclose and describe this perspective is very difficult. We know that public services themselves, and even the state itself, and commercial organizations manage to conceal the true information about the attack in their information system security and the consequences of such an attack on the investigating authorities and the public. For this reason, it is necessary and important information for investigation remains a mystery.Key words: information security, information crimes, criminalistics, the investigation, the investigation of the situation, tactical actions investigative, computer forensics and technology, using of special knowledge.